2012
DOI: 10.3892/ol.2012.703
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of heparanase multiple antigenic peptide 2 is associated with poor prognosis in gastric cancer: Potential for therapy

Abstract: Abstract. Tumor-associated antigens (TAAs) trigger a TAA-specific immune response, thus they are the crux of antitumor immunosurveillance. A major advance in tumor immunology in the last 20 years was marked by the verification that CTL or B-cell epitopes rather than integral TAAs induce immunoreactivity. Previous studies on the correlation between heparanase (Hpa) expression and clinical or pathological features have generally used commercial antibodies against full-length Hpa protein rather than the functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…In the present study, it was revealed that positive expression of HPA was able to predict the malignancy of GC due to its correlation with lymphatic metastasis and invasive depth. Beyond that, positive expression of HPA was a poor prognostic factor for overall survival and relapse-free survival compared with HPA negative cases, which was consistent with previously published reports[ 52 ]. Especially in GC patients with an obvious H. pylori infection, HPA positive expression indicated a poorer prognosis both in overall survival and in relapse-free survival, which illustrates that HPA is an important factor for the prediction of prognosis and relapse of GC and that H. pylori infection leads to an increase of HPA expression, which can worsen the prognosis of GC and make recurrence more likely.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, it was revealed that positive expression of HPA was able to predict the malignancy of GC due to its correlation with lymphatic metastasis and invasive depth. Beyond that, positive expression of HPA was a poor prognostic factor for overall survival and relapse-free survival compared with HPA negative cases, which was consistent with previously published reports[ 52 ]. Especially in GC patients with an obvious H. pylori infection, HPA positive expression indicated a poorer prognosis both in overall survival and in relapse-free survival, which illustrates that HPA is an important factor for the prediction of prognosis and relapse of GC and that H. pylori infection leads to an increase of HPA expression, which can worsen the prognosis of GC and make recurrence more likely.…”
Section: Discussionsupporting
confidence: 92%
“…The present study was based on previous investigations of a heparanase MAP vaccination strategy (18)(19)(20)(21)(22), with the establishment of a method to induce a high-titer humoral immune response (23). To achieve the inhibition of TNF-α, internet software was used to predict the TNF-α B-cell epitope and an optimized immunization strategy (MAP + T cell epitope peptide) was used to induce high titers of antibody in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the reported anti-inflammatory effects of heparin (Young, 2008), increased levels of highly sulfated, “heparin-resembling” HS fragments, which are constantly present in Hpa-tg , as compared to wt mice (Escobar Galvis et al, 2007b; Li et al, 2005), may offer an explanation for the inhibitory effects of continuous heparanase overexpression on neutrophils in these settings (Li et al, 2012a; Zhang et al, 2012a). In addition, it was noted that the thickness of the glycocalyx varies greatly between microvessels from different tissues: it is almost 3 times thinner in cremaster (systemic) microvessels endothelium than in pulmonary endothelium (Schmidt et al, 2012).…”
Section: Heparanase In Acute and Chronic Inflammationmentioning
confidence: 99%